2020
DOI: 10.24042/ajpm.v11i1.6620
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Cooperative learning method and Students’ Mathematics Learning Achievement: A Meta-Analysis Correlation

Abstract: An appropriate learning method can improve students’ learning achievement. The cooperative learning method encourages students to improve their mathematics learning achievement. Mathematics learning achievement is one indicator of achieving learning objectives. Mathematics is an important lesson to be learned and must be mastered by students. The purpose of this research was to analyze the effect size of the relationship between Cooperative learning method and mathematics learning achievement through meta-anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(19 citation statements)
references
References 37 publications
1
17
0
1
Order By: Relevance
“…Cooperative learning has a negligible effect of 0.445 in mathematics courses and a medium effect of 0.558 in high school. The same meta-analysis review found a 0.15 measure of the effectiveness of cooperative learning on students' mathematics learning outcomes (Setiana et al, 2020). The effect size of cooperative learning on students' cognitive capacities is 1.213 in the strong category (Alacapınar & Uysal, 2020).…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…Cooperative learning has a negligible effect of 0.445 in mathematics courses and a medium effect of 0.558 in high school. The same meta-analysis review found a 0.15 measure of the effectiveness of cooperative learning on students' mathematics learning outcomes (Setiana et al, 2020). The effect size of cooperative learning on students' cognitive capacities is 1.213 in the strong category (Alacapınar & Uysal, 2020).…”
Section: Discussionmentioning
confidence: 95%
“…Other research shows that grouping research articles published in SINTA and GARUDA-indexed journals have an appropriate measure of 1.04, higher than grouping papers published in Google Scholar-indexed journals or proceedings. The meta-analysis review is only based on the variables of education level, the field of study, culture, the field of mathematics, cooperative learning techniques used, and duration of mathematics learning (Agustini et al, 2021;Capar & Tarim, 2015;Kyndt et al, 2013;Mansurah et al, 2021;Setiana et al, 2020;Turgut & Turgut, 2018) and based on cognitive, affective, and psychomotor abilities (Alacapınar & Uysal, 2020). Kyndt et al (2013) employed moderator variables based on education level, study field, and culture.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Hipotenusa Journal, 3 (1), June 2021 Haerudin, Dewi Anjani, Didymus Ibrahi Thus directing students in learning mathematics is important so that understanding the concepts that will be needed to solve mathematics and other sciences (Setiana et al, 2020;Tomperi et al, 2020). For this reason, students need to have mathematical abilities.…”
Section: Law Number 20 Of 2003 Concerning the National Education System Shows Thatmentioning
confidence: 99%